The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.5863/1551-6776-9.4.226
|View full text |Cite
|
Sign up to set email alerts
|

MDI versus Nebulizers for Acute Asthma

Abstract: OBJECTIVE: To evaluate studies comparing metered dose inhalers with holding chambers to nebulizers in the emergency department for the treatment of asthma exacerbation. DATA SOURCE: Primary articles and systematic review provided by the Cochrane Airways Review Group of the Cochrane Library identified by MEDLINE search (1966–February 2004) and through secondary sources. DATA SYNTHESIS: The Cochrane review included 21 randomized clinical trials conducted in hospital emergency depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…This included personal protective equipment, disinfectant wipes, and basic medical equipment, such as pulse oximeters, blood pressure cuffs, thermometers, oxygen tanks, and locked medication bins to store common medications such as fever reducers and albuterol metered-dose inhalers. Nebulizer treatments were not permitted due to the risk of COVID-19 transmission (Benge & Barwise, 2020), and a Cochrane review found that metered-dose inhalers with spacers are at least as effective as nebulized medications (Raissy & Kelly, 2004).…”
Section: Surge Space Equipmentmentioning
confidence: 99%
“…This included personal protective equipment, disinfectant wipes, and basic medical equipment, such as pulse oximeters, blood pressure cuffs, thermometers, oxygen tanks, and locked medication bins to store common medications such as fever reducers and albuterol metered-dose inhalers. Nebulizer treatments were not permitted due to the risk of COVID-19 transmission (Benge & Barwise, 2020), and a Cochrane review found that metered-dose inhalers with spacers are at least as effective as nebulized medications (Raissy & Kelly, 2004).…”
Section: Surge Space Equipmentmentioning
confidence: 99%